Identification of the epsilon-subunit of Escherichia coli DNA polymerase III holoenzyme as the dnaQ gene product: a fidelity subunit for DNA replication. - Scheuermann, R (1983)
Based on extensive genetic and biochemical studies, the multisubunit DNA polymerase III holoenzyme is considered responsible for the chain-elongation stage in replication of the genome of Escherichia coli and is thus expected to be the major determinant of fidelity as well. Previous experiments have shown that two mutations conferring a very high mutation rate on E. coli, mutD5 and dnaQ49, decrease severely the 3' leads to 5' exonucleolytic editing activity of the polymerase III holoenzyme. To identify more precisely the nature of these mutations, we have carried out genetic mapping and complementation experiments. From these studies and experiments by others, we conclude that the most potent general mutator mutations in E. coli occur in a single gene, dnaQ. To define further the role of the dnaQ gene, we have used two-dimensional gel electrophoresis to compare the labeled dnaQ gene product with purified polymerase III holoenzyme. The dnaQ product comigrates with the epsilon-subunit, a 25-kilodalton protein of the polymerase III "core" enzyme. We conclude that the epsilon-subunit of polymerase III holoenzyme has a special role in defining the accuracy of DNA replication, probably through control of the 3' leads to 5' exonuclease activity.